Work-related stress of companies' directors during the first lockdown due to the COVID-19 - Dutheil, Frédéric; Jeanton, Carole; Vilmant, Audrey; Lambert, Céline; Clinchamps, Maelys; Ugbolue, Ukadike Chris; Schmidt, Jeannot; Vallet, Guillaume T.; Bouillon-Minois, Jean-Baptiste (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic and the first lockdown were particularly stressful with a major economic impact, but the impact on stress of company directors was not known. Therefore, this study aimed to assess that impact and the characteristics of companies the most at risk. Method: A online questionnaire was sent to 13,114 company. It assessed stress at work, number of employees, sector of activity, business activity rate and geographical location. It studied the mean stress levels, the percentage of stress > 8/10 and carried out an analysis of the characteristics of the most at-risk companies. Results: A total of 807 company directors responded. Their stress levels increased by 25.9% during lockdown and 28.7% of them had a stress > 8/10. Sectors which had the biggest increase in stress levels during lockdown were retail trade, wholesale trade, and nursing homes. Sectors the most at risk of stress >8/10 during lockdown tended to be nursing homes, pharmacies, and IT activities. Biggest companies had the highest increase in stress levels. Conclusion: The first lockdown of the COVID-19 pandemic had a major impact on the stress of company directors. Directors of large companies were the most exposed to stress as well as medical and IT activities.